Contractual business partnership in Islamic law: a comparison of critical theoretical aspects - Sadique, Muhammad Abdurrahman (Edusage Network, 2019)
With regard to the two major divisions of partnership or shirkah in Islamic law, the type which is more relevant to business and commerce is shirkah al-‘aqd or contractual partnership. This is the type that is principally applied in all forms of financing undertaken by Islamic financial institutions. Islamic law has a well formulated system of requirements and rules governing this form of partnership, that attempts to ensure the formation, operation and conclusion of the contractual relationship of the partners taking place on a just and equitable foundation, ruling out violation of the rights of any. Thus, the principle criteria lay down the conditions and rules that should be observed with regard to the partners, capital, profit division, management, rights of partners as well as liquidation and invalidity. While the schools of Islamic law have different approaches to many of these issues based on fundamental precepts derived from the holy Qur’an and the prophetic traditions, each school provides a complete and coherent system that is well-balanced and equitable. The current paper attempts to provide a brief and clear comparison of the positions of the schools of Islamic law on the major aspects pertaining to commercial partnership, as portrayed in the major works of each school.